THE EFFICIENCY OF EXTRACURRICULAR ACTIVITIES IN SCHOOL LANGUAGE LEARNING - Karimiva Kumush; Rasulova Sokhiba (Western European Studies, 2024)
Extracurricular activities (ECA) are usually defined as learners’ activities that fall outside the normal curriculum of educational institution, they supplement the regular course of classroom instruction and are sometimes organized or conducted with some participation of instructors (Campbell, 1973). In the field of applied linguistics and education, there is a general agreement to encourage extracurricular activities at school programs for language learners of different majors, because ECA help them to develop important skills, such as leadership, socializing, character training, and others.
Keywords: Language teaching; culture; competence